The impact of climate change on the variation in area, yield, and production of some field crops in Diyala Governorate (1970 - 2022) - Chlobe , Zainab (Al-Adab Journal, 2025)
The research aims to know the impact of climate change on some field crops, namely (wheat - rice - yellow corn - barley), by identifying the most important changes that affected the area, yield and productivity of each crop, as these crops are affected by the changes that occur in the climatic elements, whether Negative or positive, which is reflected in their numbers and productivity. Data on climate factors (solar brightness - temperatures - winds - air humidity -rain- evaporation) were divided into climate cycles, each cycle representing ten years.The research reached a number of results, including the presence of an increase and decrease between the area, yield and production of crops. The cycle between (1971-1981) and (1982-1992) witnessed the area planted with wheat reaching (-4%) and the yield (-20%), while production (603.3%, and the cycle between (1971-1981) and (1982-1992) witnessed a percentage of (65%) in the area planted with barley and yield (-9%), while production (53%). As for the cycle between (1982-1992) -(1993-2004) The cultivated area recorded a rate of (-44%), yields (5%), and production (-58%), while in the cycle between (1993-2003) -(2004-2022), the area recorded a rate of (-63%) %) and yield (132%) while production by (-21%).